Glastonbury Abbey
In earlier Norman building, stone was worked with axe, which rapidly shaped small quarried blocks; but in the later periods, improvements in hoisting techniques learned from visits to the Middle East on Crusades and the use of the chisel began to influence design. William of Malmesbury, the twelfth century historian from whose writing much of Norman and Saxon affairs is known, says that in his day stone was so well and truly laid that one might think the building was cut from one block.